Technical Note: Comparison between a direct and the standard, indirect method for dissolved organic nitrogen determination in freshwater environments with high dissolved inorganic nitrogen concentrations - D. Graeber; J. Gelbrecht; B. Kronvang; B. Gücker; M. T. Pusch; E. Zwirnmann (Biogeosciences, 2012)
Research on dissolved organic nitrogen (DON) in aquatic systems with high dissolved inorganic nitrogen (DIN, the sum of NO3–, NO2– and NH4+) concentrations is often hampered by high uncertainties regarding the determined DON concentration. The reason is that DON is determined indirectly as the difference between total dissolved nitrogen (TDN) and DIN. In this standard approach to determine DON concentrations, even small relative measurement errors of the DIN and TDN concentrations propagate into high absolute errors of DON concentrations at high DIN : TDN ratios. To improve the DON measurement accuracy at high DIN : TDN ratios, we investigated the DON measurement accuracy of this standard approach according to the DIN : TDN ratio and compared it to the direct measurement of DON by size-exclusion chromatography (SEC) for freshwater systems. For this, we used standard compounds and natural samples with and without DIN enrichment. We show that for the standard approach, large errors of the determined DON concentrations at DIN : TDN ratios >0.6 occur for both standard compounds and natural samples. In contrast, measurements of DON by SEC always gave low errors at high DIN : TDN ratios due to the successful separation of DON from DIN. For SEC, DON recovery rates were 91–108% for five pure standard compounds and 89–103% for two standard compounds, enriched with DIN. Moreover, SEC resulted in 93–108% recovery rates for DON concentrations of natural samples at a DIN : TDN ratio of 0.8 and the technique was successfully applied to a range of samples from waste water treatment plants to forest and agricultural streams. With 2.5 h of measurement time per sample, SEC is slower, but more accurate than the standard approach for determination of DON concentrations in freshwaters with DIN : TDN ratios >0.6. To sum up, the direct DON measurement by SEC enables better understanding of the nitrogen cycle of urban and agricultural freshwater systems.